2017
DOI: 10.1176/appi.ps.201600217
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action for Obtaining Job Offers With Virtual Reality Job Interview Training

Abstract: Objective Four randomized controlled trials (RCTs) revealed that virtual reality job interview training (VR-JIT) improved interviewing skills and the odds of obtaining a job offer among trainees with severe mental illness or autism spectrum disorder. This study assessed whether post-intervention interviewing skills mediated the relationship between virtual interview trial completion and receiving job offers by 6-month follow-up. Methods VR-JIT trainees (n=79) completed pre- and post-test role-plays and a bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 14 publications
4
11
0
8
Order By: Relevance
“…Most research using these protocols does not use self-report questionnaires specific to anxiety in a job interview, thus, the MASI-P may be more focused and helpful for understanding the specific difficulties people may feel in job interview circumstances. Recent studies using virtual reality have shown promising results, such as the improvement of socioemotional competencies, interviewing competencies, less anxiety, and better performance (e.g., Langer et al, 2016;Smith et al, 2017). Teaching interviewees how to promote themselves, paradoxically, can help interviewers to more accurately understand a candidate's best qualities, allowing more valid interview decisions (Macan, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most research using these protocols does not use self-report questionnaires specific to anxiety in a job interview, thus, the MASI-P may be more focused and helpful for understanding the specific difficulties people may feel in job interview circumstances. Recent studies using virtual reality have shown promising results, such as the improvement of socioemotional competencies, interviewing competencies, less anxiety, and better performance (e.g., Langer et al, 2016;Smith et al, 2017). Teaching interviewees how to promote themselves, paradoxically, can help interviewers to more accurately understand a candidate's best qualities, allowing more valid interview decisions (Macan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Job interview competencies may also contribute to decreasing anxiety. Several authors have shown how training job interview competencies before a selection process can be important to foster confidence, reduce anxiety and contribute to a better performance (Langer et al, 2016;Macan, 2009;Smith et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These technologies have also improved the quality of life for workers through remote monitoring, assistance, and vigilance. In addition, there are a wide variety of emerging technologies that allow the hybridization of the real and virtual world, such as sensors in products and processes [ 46 ], Bluetooth devices to detect parameters, wearables [ 47 ], collaborative robotics and automation [ 48 ], self-monitoring for inclusion in the work environment [ 49 ], virtual reality for employability and interviews [ 50 ], virtual training agents [ 51 ], process simulation and virtualization [ 52 ], social networks, advanced cloud computing, digital twins, and collaborative platforms. These technologies allow a symbiosis between the applications or enabling technologies in the workplace, which can be employed to assist in the development of the tasks, monitoring, and supervision of the worker in a personalized way and in the work done in real time.…”
Section: Background Of Literaturementioning
confidence: 99%
“…Mittlerweile ist die VR-Technik so weit fortgeschritten, dass eine glaubwürdige soziale Interaktion simuliert werden kann [45,46]. Erste Hinweise auf die Wirksamkeit eines Trainings von Vorstellungsgesprächen in VR liegen für verschiedene Patientengruppen vor [47]. Soziale Interaktion ist auch Kernelement eines innovativen VR-Ansatzes, der chronisches Stimmenhören im Rahmen psychotischer Erkrankungen reduzieren soll.…”
Section: Weitere Anwendungenunclassified